Nanoscale correlative X-ray spectroscopy and ptychography of carious dental enamel - Cyril Besnard; Ali Marie; Sisini Sasidharan; Petr Buček; Jessica M. Walker; Julia E. Parker; Thomas E.J. Moxham; Benedikt Daurer; Burkhard Kaulich; Majid Kazemian; Richard M. Shelton; Gabriel Landini; et al. (Materials & Design, 2022)
This study reports the characterisation of human dental enamel caries using synchrotron nanoscale correlative ptychography and spectroscopic mapping in combination with scanning electron microscopy. A lamella ̴2.4 µm thick was extracted from a carious enamel region of a tooth using focused ion beam-scanning electron microscopy and transferred to two synchrotron beamlines to perform hard X-ray nano-fluorescence spectroscopy simultaneously with differential phase contrast mapping at a beam size of 55 × 45 nm. Soft X-ray ptychography data was then reconstructed with a pixel size of 8 nm. The two dimensional variation in chemistry and structure of carious enamel was revealed at the nanoscale, namely, the organisation of hydroxyapatite nano-crystals within enamel rods was imaged together with the inter-rod region. Correlative use of electron and X-ray scanning microscopies for the same sample allowed visualisation of the connection between structure and composition as presented in a compound image where colour indicates the relative calcium concentration in the sample, as indicated by the calcium Kα fluorescence intensity and grey scale shows the nanostructure. This highlights the importance of advanced correlative imaging to investigate the complex structure-composition relationships in nanomaterials of natural or artificial origin.